UNVEILING THE DRIVERS OF CORPORATE BOND RATINGS: EVIDENCE FROM EMERGING AND DEVELOPED MARKETS - Diana Teresa; Patricia Diana (Universitas Katolik Indonesia Atma Jaya, 2026)
This study was conducted to obtain empirical evidence on the influence of company size proxied by total assets (TA), profitability proxied by return on assets (ROA), bond age proxied by dummy variable, leverage proxied by debt to equity ratio (DER), and liquidity proxied by current ratio (CR) on bond ratings. The object of this study is non-financial companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2022 and issuing bonds rated by PT Pemeringkat Efek Indonesia (PEFINDO) from 2021 to 2023.The sample selection was done using the purposive sampling method resulting in a total of 18 non-financial companies. The data used in this study were secondary data, namely financial statements and a list of bond ratings issued by PT PEFINDO. The data analysis was conducted using SPSS version 26. The data analysis method used was ordinal logistic regression, a method used in research with dependent variables in ordinal form (ratings). The results of the study indicate that (1) company size proxied by total assets has a positive and significant effect on bond ratings; (2) profitability proxied by ROA has a positive and significant effect on bond ratings; (3) bond age proxied by dummy variable has no significant effect on bond ratings; (4) leverage proxied by DER has a negative and significant effect on bond ratings; (5) liquidity proxied by CR has no significant effect on bond ratings.